90 Penetrating Abdominal Trauma: Comperative Study Between Operative and Conservative Management. (12th October 2021) - Shalaby, A; Ibrahim, M; El Faioumy, T; Elmessiry, M
Abstract: Aim: to Assess the feasibility and safety of selective non-operative management in penetrating abdominal injuries and to identify a protocol for selection of patient's candidates for non-operative management. Method: In this comparative study 40 abdominal stab victims (admitted to Emergency Department of Alexandria Main University Hospital) were selected during 6 months period where 20 patients were suitable for non-operative management according to strict selection criteria whereas the other 20 patients were operated according to clinical and/or radiological indications or on basis of department protocol, the results were compared in view of final outcome. Results: In our study, 15 patients were assigned for operative management according to selected clinical and/or radiological indications only 3 of them (20%) had non-therapeutic laparotomies, On the other hand, five patients were explored on basis of department protocol in violation of our indications for exploration; four of them (80%) were non-therapeutic. So, the rate of non-therapeutic laparotomies was significantly higher when done mandatory without selected clinical and radiological indications. Conclusions: Assessment of vital signs together with abdominal examination are the most important and dependable tools in decision making in penetrating abdominal trauma patients. Patients with shock on admission (but responding to resuscitation), proved low grade solid organ injury (by CT), and proved intraperitoneal collection (by US or CT) could be managed conservatively regarding that they remain vitally and clinically stable. If failure of conservation occurs, it is usually during the 1st 24 hours after admission.